Analysis of Perceived Benefit of Video on Demand Subscription - Rahmi; Amalia Nabila; Gusty Mutiara Medina (LPPM Universitas Negeri Jakarta, 2024)
This study examines the perceived benefits of Video on Demand (VoD) services through two main dimensions: perceived usefulness and perceived enjoyment. A cross-sectional questionnaire survey design was adopted in this study. An online version of the survey was developed using Google Forms, and a survey link was generated. The 244 respondents of this study are those who are familiar with Video on Demand products. Analysis methods included validity and reliability testing using SPSS version 26, as well as calculating the weighted average and scale range to assess the effectiveness of perceived benefits. Results indicate that both dimensions, perceived usefulness and perceived enjoyment, fall into the